Nurse Practitioners and Virtual Care: A 50-State Review of APRN Telehealth Law and Policy - Garber, Kelli M.; Chike-Harris, Katherine E. (Telehealth and Medicine Today, 2019)
The healthcare industry is bracing for a predicted shortage of primary care physicians at a time when the telehealth industry is predicted to explode. Advance practice registered nurses (APRNs), who combine clinical expertise with an added emphasis on disease prevention and health management, have long been providing high-quality healthcare in the United States and will likely play a key role in assisting to alleviate this anticipated shortage. Approximately 86% of APRNs are certified in an area of primary care, and the workforce continues to grow with over 26,000 new APRNs completing their academic programs in 2017. Empowering APRNs to provide care via telehealth will extend the reach of their expertise and further expand access to care. Before providing care via telehealth, APRNs must be well versed in the laws, regulations, and policies affecting their practice when using this modality, especially since these can vary significantly between states. To this end, a 50-state review of APRN legislation, advisory opinions, policy statements, and telehealth legislation as it pertains to APRNs was conducted. The findings illustrate a wide array of APRN telehealth policies and regulations, ranging from no APRN telehealth provisions to detailed guidelines established in statute. State-by-state findings are summarized while identifying the various resources that should be considered when reviewing APRN telehealth practice policy. Recommendations to foster telehealth adoption by APRNs through legislative means are also provided.